Determinants of credit constraints and its impact on the adoption of climate change adaptation strategies among rice farmers in South-West Nigeria - T. O. Ojo; L. J. S. Baiyegunhi (Journal of Economic Structures, 2020)
Interventions on climate change adaptation strategies, involve capital outlays, mostly constrained in supply in developing nations. This study analysed the impact of credit constraints on climate change adaptation strategies among smallholder rice farmers in South-West Nigeria. The nexus between systems of credit constraints and choice of climate change adaptation strategies was estimated using Generalized Method of Moments with Instrumental Variable (IV-GMM) and the seemingly unrelated regression (SUR) model. A principal component analysis (PCA) was used to reduce the multidi-mensionality of the adaptation strategies and the loading with the highest eigenvalue was chosen and renamed as an improved technology. The results of the study show that risk credit-constrained smallholder rice farmers are less likely to adopt climate change adaptation strategies. The quantitative analysis from this study also points to the fact that age of the household, source of credit, and distance to the source of credit, interest rate, access to extension and climate information were the determi-nants of credit constraint amongst the smallholder rice farmers in South-West Nigeria. Considering the nexus between climatic factors and credit constraints as noted in this study, increasing awareness about how the credit market works and information on the provision of climate change can help farmers to better adapt to climate change. Therefore, it is recommended that the government frame an agriculture credit policy addressing the issues of smallholder farmers, particularly in areas that are vulnerable to climate change. The income from non-farm activities can be reinvested into farm oper-ations to improve farmers' adaptive capacity and subsequently increase productivity. It could also be recommended that policies enhancing and strengthening institutional support may also be valuable in augmenting the adaptation strategies of smallholder farmers. A necessary addition should be developed to the assistance already being provided under Nigeria Incentive-Based Risk Sharing System for Agricultural Lending (NIRSAL) in the form of loan guarantees and other risk-sharing incentives, such as a regulatory environment that supports the modern contractual obligations that are characteristic of well-functioning agricultural financing.
Keywords: 330; Credit constraint; Climate change; Adaptation strategies; IV-GMM and SUR